Teachers’ Performance in Science Learning Management Integrated with Character Education (Jurnal Pendidikan IPA Indonesia, 2018)
The research aims at revealing the performance of teachers in science learning management integrated with character education. This study employed qualitative research method. Based on the result of the t-test of the correlation coefficient, this study obtained t value 4,210 with significance 0,001. The significance value 0,001 0,05 showed that there is influence from teachers’ performance in arranging learning media integrated with character education to the teachers’ performance in science learning. The conclusion of research stated that the performance of science teachers in junior high schools in Semarang City in integrating character education is categorized into a very good category with average score 85,05.